109 OUTCOMES FOLLOWING NECK OF FEMUR FRACTURES IN A UNIVERSITY TEACHING HOSPITAL. (18th November 2021) - Sullivan, R; McCauley, H; Macgregor, B; Mulpeter, K
Abstract: Background: Neck of femur (NOF) fractures cause significant morbidity and mortality. Many require off site rehabilitation and it can lead to a new functional baseline with increased care needs. The objective of this study was to explore this impact on patients with NOF fractures in a university teaching hospital. Methods: This retrospective observational study was performed on admitted patients with NOF fractures in 2019. Using a structured proforma, data was collected from the patients' electronic record and from follow up telephone consultations at one year. Frailty and functional capacity was assessed at one year using the Clinical Frailty Scale and the Barthel Index. Results: 123 patients had a NOF fracture from January to December 2019. The female to men ratio was 2:1 and the average age was 79 years. The majority of patients were admitted from home (86%). At baseline, 58% mobilised independently without aids. On discharge, 39% were transferred to offsite rehab, 41% discharged home and 13% were discharged to a nursing home. At one year, the mortality rate was 26% which is comparable with other studies [1]. 30% had a new home care package and 19.4% were in a nursing home. 75% were readmitted with a third due to falls. On average, patients were classified as mild to moderately frail (CFS of 4.84) with moderate dependency (Barthel Index of 76.5). Conclusion: Hip fractures have a high mortality rate and have a significant impact on patient's function with a third requiring extra support at home and a fifth requiring a nursing home admission. Frailty tools may be useful to help predict outcomes in the future. Reference: 1. Schell et al., The 1-Year Mortality of Patients Treated in a Hip Fracture Program for Elders, Geriatr Orthop Surg Rehabil. 2010 Sep; 1(1): 6–14.